Architects of Occupation : American Experts and Planning for Postwar Japan - Barnes, Dayna L., 1982- (Book collections on Project MUSE., 2017)
The Allied occupation of Japan is remembered as the 'good occupation.' An American-led coalition successfully turned a militaristic enemy into a stable and democratically. Of course, the story was more complicated, but the occupation did forge one of the most enduring relationships in the postwar world. Recent events, from the occupations of Iraq and Afghanistan to protests over American bases in Japan to increasingly aggressive territorial disputes between Asian nations over islands in the Pacific, have brought attention back to the subject of the occupation of Japan. In 'Architects of Occupation', Dayna L. Barnes exposes the wartime origins of occupation policy and broader plans for postwar Japan. She considers the role of presidents, bureaucrats, think tanks, the media, and Congress in policymaking.